Lymphoproliferative malignancies in patients with neurofibromatosis 1 - Bergqvist, Christina (Orphanet J Rare Dis, 2021)
Neurofibromatosis 1 (NF1) is an inherited, autosomal-dominant, tumor predisposition syndrome with a birth incidence as high as 1:2000. A patient with NF1 is four to five times more likely to develop a malignancy as compared to the general population. The number of epidemiologic studies on lymphoproliferative malignancies in patients with NF1 is limited. The aim of this study was to determine the incidence rate of lymphoproliferative malignancies (lymphoma and leukemia) in NF1 patients followed in our referral center for neurofibromatoses. We used the Informatics for Integrated Biology and the Bedside (i2b2) platform to extract information from the hospital’s electronic health records. We performed a keyword search on clinical notes generated between Jan/01/2014 and May/11/2020 for patients aged 18 years or older. A total of 1507 patients with confirmed NF1 patients aged 18 years and above were identified (mean age 39.2 years; 57% women). The total number of person-years in follow-up was 57,736 (men, 24,327 years; women, 33,409 years). Mean length of follow-up was 38.3 years (median, 36 years). A total of 13 patients had a medical history of either lymphoma or leukemia, yielding an overall incidence rate of 22.5 per 100,000 (0.000225, 95% confidence interval (CI) 0.000223–0.000227). This incidence is similar to that of the general population in France (standardized incidence ratio 1.07, 95% CI 0.60–1.79). Four patients had a medical history leukemia and 9 patients had a medical history of lymphoma of which 7 had non-Hodgkin lymphoma, and 2 had Hodgkin lymphoma. Our results show that adults with NF1 do not have an increased tendency to develop lymphoproliferative malignancies, in contrast to the general increased risk of malignancy. While our results are consistent with the recent population-based study in Finland, they are in contrast with the larger population-based study in England whereby NF1 individuals were found to be 3 times more likely to develop both non-Hodgkin lymphoma and lymphocytic leukemia. Large-scale epidemiological studies based on nationwide data sets are thus needed to confirm our findings.